FACTORS INFLUENCING DETERMINATION OF SPACE RENTAL FOR ATM IN PEKANBARU CITY - Luthfi, Faiz (Jurnal BPPK: Badan Pendidikan dan Pelatihan Keuangan, 2023)
Government valuers have a role in the process of utilizing state assets, one of which is the rent of state assets for ATM placement spaces. However, the unique characteristics of the property make the determination of factors in this valuation vary from appraiser to appraiser, which can result in biased values that can lead to the failure of state asset rents if the lease value is too expensive and fails to be absorbed by the market. This study uses an exploratory factor analysis method with samples of 112 ATM space rental units scattered surround the area of Pekanbaru City. The results of this study show that 12 variables can be simplified into four major factors that can influence the determination of ATM space rental in Pekanbaru City. These factors are (1) Accessibility, (2) Position and layout, (3) Location and attractiveness, and (4) Environment and facilities. Of these factors, accessibility is the most influential factor. The results of this study can be a reference for valuers in determining the factors that influence the lease of state assets for ATM space.